Bartonella spp. in Small Mammals and Their Fleas in Differently Structured Habitats From Germany - Obiegala, Anna; Pfeffer, Martin; Kiefer, Daniel; Kiefer, Matthias; Król, Nina; Silaghi, Cornelia (Frontiers in Veterinary Science, 2021)
Most Bartonella spp. are transmitted by fleas and harbored by small mammals which serve as reservoirs. However, little is known about the composition of fleas and their Bartonella spp. from small mammals in Central Europe. Therefore, the aims of this study were to investigate flea communities on small mammals from three differently structured sites (urban, sylvatic, renatured) in Germany as well as the prevalence of Bartonella spp. in small mammals and their parasitizing fleas. In total, 623 small mammals belonging to 10 different species (the majority were Myodes glareolus and Apodemus flavicollis) were available. Fleas were removed from the small mammals' fur, morphologically identified and DNA was extracted. To detect Bartonella spp., two conventional PCRs targeting the gltA gene and the 16S−23S rRNA intergenic spacer were carried out followed by sequencing. Obtained sequences were compared to those in GenBank. In total, 1,156 fleas were collected from 456 small mammals. Altogether, 12 different flea species (the majority were Ctenophthalmus agyrtes, Nosopsyllus fasciatus, and Megabothris turbidus) were detected. At the urban site mostly Leptopsylla segnis and N. fasciatus were collected which may be vectors of zoonotic pathogens to companion animals. The overall prevalence for Bartonella in small mammals was 43.3% and in fleas 49.1%. Five different Bartonella spp. were detected in small mammals namely B. grahamii, B. taylorii, B. doshiae, Bartonella sp. N40 and uncultured Bartonella sp. whereas in fleas four Bartonella spp. were found which were with the exception of B. doshiae identical to the Bartonella species detected in their small mammal hosts. While B. grahamii was the only zoonotic Bartonella sp. most Bartonella strains found in fleas and small mammals belonged to uncultured Bartonella spp. with unknown zoonotic potential. This study showed a high diversity of flea species on small mammals from Germany. Further, high prevalence rates of Bartonella species were detected both in fleas and in their mammalian hosts. Several different Bartonella species with a high genetic variability were discovered. Especially at the urban study sites, this may pose a risk for Bartonella transmission to companion animals and humans.